Methodology for assessing the impact of the financial mechanism of regulating innovative activity on the innovative behavior of organizations - Klimova, Natallia P. (Journal of the Belarusian State University. Economics, 2020)
A new method for assessing the impact of the financial regulatory mechanism on the organization is proposed. Therefore, in this study, the subject is not the effectiveness of incentives or the effect of innovation, but the innovative behavior of an organization depending on the current financial policy for regulating innovation activity. A methodology is proposed and tested, which, based on the calculation of the three indices and tracking their changes over time, allows one to assess how favorable the current financial policy is for the innovation activities of individual organizations.
Keywords: innovation; financial mechanism; financial policy; tax policy; innovation activity; financial incentives